The Validity of Colloid e-Module Based STEAM Integrated with Socio-scientific Issues - Miftahul Ulum; Sudarmin Sudarmin; Sigit Priatmoko (Universitas Lampung, 2021)
The need for chemistry teaching materials with technological nuances has become a priority learning resource in the current